Hubungan PM2,5 Dan PM10 Dalam Udara Ambien Terhadap Penyakit Infeksi Saluran Pernapasan Akut (Studi Kasus Desa Tanjung Jambu Kecamatan Merapi Timur Kabupaten Lahat) - Jerri Agustan; lukitowati hariani, poedji; Novrikasari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
The increase in coal mining activities in Lahat Regency, South Sumatra Province continues to increase, which has an impact on Tanjung Jambu Village which is a portal for special road entry for lifting and transporting coal. This of course has the potential to result in a decrease in ambient air quality. This study aims to determine the relationship between PM2.5 and PM10, as well as to examine the physical environmental factors and community behavior at the productive age of 15-64 years to the increase in the incidence of ISPA, to further provide recommendations and control strategies. This study used an analytical observational study design with crosss sectional, samples were selected by stratified random system, Particulate Matter (PM) data was collected directly using High Volume Air Sampler (HVAS) at two sample points with a distance of <50m and >50m from the road, data on Acute Respiratory Tract Infection (ARI), physical condition of the environment and community behavior were obtained from the results of observations and interviews through questionnaires. The results showed that the concentration of PM2.5 PM10 met the requirements below the environmental quality standards. that is determined. The prevalence of ARI community is 25.5%, not ARIA is 74.5%, which means there is no relationship to the increase in the incidence of ARI. Five variables of physical factors of the environment and community habits, namely ventilation, residential density, distance from the house to the road, smoking behavior, hand washing and the use of masks are not related. The variable of smoking habit had a significant relationship with the incidence of ARI (OR= 2,315; 95% CI: 1,388-4,007).